Transcatheter aortic valve implantation versus surgical aortic valve replacement in Chinese patients with intermediate and high surgical risk for aortic stenosis: a decision analysis on effect, affordability and cost-effectiveness - Chang Liu; Chong Chen; Chuanyu Gao; Xiaoyan Guo; Dan Hu; Tongfeng Chen; Yipin Zhao; Jiangtao Cheng; Yuhao Liu (BMJ Open)
Objective Examine the cost-effectiveness of transcatheter aortic valve implantation (TAVI) versus surgical aortic valve replacement (SAVR) for Chinese patients with severe aortic stenosis (AS) at intermediate and high surgical risk.Design A two-phase model, comprising a 1-month decision tree to simulate perioperative outcomes and a 5-year Markov model with monthly cycles to simulate long-term outcomes, has been developed to evaluate the cost-effectiveness of TAVI compared with SAVR for Chinese patients with AS at intermediate and high risk. The event rates for both phases are sourced from the Placement of Aortic Transcatheter Valves IA and IIA trials, while the cost inputs and utility values are sourced from local sources or published literature. Adjustments for inflation were made using consumer price indexes for healthcare to enhance precision. To ensure the reliability and robustness of the model, sensitivity analyses were conducted to assess their impact on outcomes.Setting China healthcare system perspective.Participants A hypothetical cohort of Chinese patients with AS in intermediate and high surgical risk.Interventions TAVI versus SAVR.Outcome measures Cost, quality-adjusted life-years (QALYs), life-years gained and incremental cost-effectiveness Ratio (ICER).Result For both intermediate- and high-risk AS patients, offering TAVR resulted in high healthcare costs but moderate benefits compared with SAVR. Specifically, in the intermediate-risk population, TAVR led to a 0.34 QALY increase over SAVR, with an incremental cost of $16 707.58, resulting in an ICER of $49 176.60/QALY. Similarly, in the high-risk population, TAVR showed a 0.15 QALY increase over SAVR, with an incremental cost of $18 093.52, leading to an ICER of $122 696.37/QALY. However, both ICERs exceeded the willingness-to-pay threshold of $37 654.50/QALY. Sensitivity analyses confirmed the model’s stability under parameter uncertainty.Conclusion TAVI was deemed not cost-effective compared with SAVR for patients with AS at intermediate or high surgical risk in the Chinese healthcare system. Lowering valve costs was considered an effective approach to improve the cost-effectiveness of TAVI.